Water Stability of Newly Formulated Pelleted Feeds - J.K., Manissery; S.K., Das; T.J., Varghese (Fishery Technology, 2025)
Formulation of suitable cost effective nutritious feed is of paramount importance in boosting fish production through aquaculture. In the present study four formulated pelleted feeds incorporating, Eichhomia, Colocasia or Gliricidia leaf powders and fishmeal were tested for water stability. All the pellets except the Gliricidia leaf powder incorporated feed showed the required stability.